Monocular Concurrent Recovery of Structure and Motion Scene Flow - Mitiche, Amar; Mathlouthi, Yosra; Ben Ayed, Ismail (Frontiers in ICT, 2015)
This paper describes a variational method of joint three-dimensional structure and motion scene flow recovery from a single image sequence. A basic scheme is developed by minimizing a functional with a term of conformity of scene flow and depth to the image sequence spatiotemporal variations, and quadratic smoothness regularization terms. The data term follows by rewriting optical velocity in the optical flow gradient constraint in terms of scene flow and depth. As a result, this problem statement is analogous to the classical Horn and Schunck optical flow formulation except that it involves scene flow and depth rather than image motion. When discretized, the Euler–Lagrange equations give a large scale sparse system of linear equations in the unknowns of the scene flow three coordinates and depth. The equations can be ordered in such a way that the corresponding matrix is symmetric positive definite, so that they can be solved efficiently by Gauss–Seidel iterations. Experiments are shown to verify the scheme’s validity and efficiency.